LGU initiative and co-management In Magat watershed in Nueva Vizcaya - Inocencio, Arlene B. (Animo Repository, 2011)
The sustainability of Magat watershed is based on a com-management model of local government units and the government environment agency in partnership with stakeholders. Enabling policy and other institutional support focus on socio-economic and cultural well-being, make all stakeholders winners